The Origin of Cognitive Linguistics and the Specificity of Linguistic Knowledge - Utanova Vazirakhon Makhmudjon kizi (Peerian Journals Publishing, 2022)
This article discusses the current importance of cognitive linguistics and its application to modern linguistics, which is a topical area of linguistics that has been discussed by scholars.
Keywords: cognitive; hypothesis; linguistics; mind